Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M F; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M. F.; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Relationship between leaf life-span and photosynthetic activity of Quercus ilex in polluted urban areas (Rome). - Gratani, L; Crescente, M F; Petruzzi, M (Environmental pollution (Barking, Essex : 1987), 2000)
Anatomical, morphological and physiological leaf traits of Quercus ilex in response to different traffic levels (high traffic level, type A sites; average traffic level, type B sites; control sites, type C sites) were analysed in Rome. Superficial leaf deposits were analysed comparing unwashed and washed leaf samples. Washing lowered Pb 61% in A, 54% in B and 27% in C. Sr, Fe, Cu, Zn and Al showed the same trend as Pb. The higher photosynthetic activity of 1-year-old leaves (Pn=7.0+/-2.9 micromol m(-2 )s(-1), average value) in A sites with respect to B sites (6.7+/-2.4 micromol m(-2 )s(-1)) and C sites (6.7+/-1.8 micromol m(-2 )s(-1)) seems to be related to higher stomatal conductance (g(s)=0.13+/-0.06 mol m(-2 )s(-1)), higher total chlorophyll content (Chl=1.57 mg g(-1)) and higher leaf thickness (L(T)=218.9 microm), particularly palisade parenchyma thickness (109.4 microm). Q. ilex showed, on average, 95% of 1-year-old leaves and rarely 2-year-old leaves in A and B sites; 77% 1-year leaves, 20% previous-year leaves and sporadic 3-year leaves in C sites. The enhanced leaf senescence in A sites is compensated by a stimulated shoot production (18% higher with respect to C sites); 25% increased specific leaf area seems to be compensatory growth occurring in order to increase the size of the assimilatory area. The inverse trend of leaf life-span and Pn seems to be Q. ilex' adaptive strategy in polluted areas.
Keywords: chlorophyll content; leaf life-span; leaf thickness; Net photosynthesis; shoot production; traffic level